Strategy for Development of the Gampong Nusa Aceh Besar Tourism Village Based on Edutourism: Community Based Tourism Approach - Wanti Nur Jadidah; Sucihatiningsih Dian Wisita P rajanti; Fadly Husain (Journal of Economic Education, 2023)
The purpose of this research is to determine the potential and problems related to the development of the Gampong Nusa Aceh Besar tourist village, the efforts that will be made by the community to optimize the potential and overcome the problems faced in developing the Gampong Nusa Aceh Besar tourist village, the role of the Gampong Nusa community and youth in supporting the development of the tourist village based on edutourism and a strategy for developing the Gampong Nusa tourist village based on edutourism with a community based tourism (CBT) approach. This research uses mixed methods, namely quantitative and qualitative with a sequential explanatory design. This design is the use of two research methods (quantitative and qualitative) in a sequence so that each method will be implemented one by one (not simultaneously) in two different research phases. The initial data collected was quantitative data, then to support this data we used qualitative data. The second analysis method is the Analytical Hierarchy Process (AHP). The research results show that Indonesia's tourism potential is so enchanting that it attracts tourists to visit Indonesia, from domestic tourists to foreign tourists. Gampong Nusa tourist village is one of the tourist villages in Aceh Province. This tourist village was awarded 1st place in the 2021 Indonesian Tourism Village Award (ADWI) in the homestay category. The homestay concept in Gampong Nusa does not change any shape of the Acehnese stilt houses. The most prioritized criteria in the Gampong Nusa Tourism Village Development Strategy Based on Edutourism with a Community Based Tourism (CBT) Approach is the tourism component with a weight value of 0.34 or 34%. In the tourism component, the most prioritized sub-criteria related to the Gampong Nusa Tourism Village Development Strategy Based on Edutourism with a Community Based Tourism (CBT) Approach are attractions with a weight value of 0.40 or 40%. In tourism management, the most prioritized sub-criteria related to the Gampong Nusa Tourism Village Development Strategy Based on Edutourism with a Community Based Tourism (CBT) Approach is the management institution with a weight value of 0.55 or 55%.